2009
DOI: 10.4314/aga.v17i1.1656
|View full text |Cite
|
Sign up to set email alerts
|

Associations culturales à base d\'hévéa : bilan de 20 années d\'expérimentations en Côte d\'Ivoire. Partie 1 : Comportement végétatif

Abstract: RESUMEDans les plantations hévéicoles en milieu non industriel de Côte d'Ivoire, le problème de la stabilisation des systèmes de cultures, à base d'hévéa (Hevea brasiliensis Muell. arg.), a été abordé sous l'angle de l'association à des cultures vivrières et industrielles. Ainsi, deux types d'associations culturales, temporaire et permanente, ont été étudiés dans la perspective d'assurer aux petits planteurs une autoconsommation familiale et éventuellement, un revenu supplémentaire pendant la période improduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
1
1
0
Order By: Relevance
“…Anguédédou and Tiassalé, being located in southern Côte d'Ivoire, are the towns that have older plantations with larger surface areas. These results are in agreement with those of Kéli et al (2005) who claim that the first rubber treeplantations were created in southeastern Côte d'Ivoire. According to Koulibaly (2014), rubber tree cultivation, which was only practiced in southern Côte d'Ivoire, has spread in recent decades to the east, center, center-west and north-west, areas formerly qualified as marginal.…”
Section: Characteristics Of the Plantations Visitedsupporting
confidence: 93%
“…Anguédédou and Tiassalé, being located in southern Côte d'Ivoire, are the towns that have older plantations with larger surface areas. These results are in agreement with those of Kéli et al (2005) who claim that the first rubber treeplantations were created in southeastern Côte d'Ivoire. According to Koulibaly (2014), rubber tree cultivation, which was only practiced in southern Côte d'Ivoire, has spread in recent decades to the east, center, center-west and north-west, areas formerly qualified as marginal.…”
Section: Characteristics Of the Plantations Visitedsupporting
confidence: 93%
“…Cette performance a été réalisée aux dépends des réserves forestières qui, par leurs apports en litière, constituaient une forte ressource minérale. Malheureusement, la dégradation des réserves forestières rendant impossible le modèle cultural extensif et itinérant sur défriche forestière, la culture du cacaoyer est restée majoritairement traditionnelle, caractérisée par le vieillissement des vergers et un faible recours aux engrais et pesticides (Kéli et Assiri, 2001 ;Assiri et al, 2012). A cela, diverses autres contraintes ont une forte emprise sur la culture du cacao.…”
Section: Introductionunclassified
“…Practices that involve intercropping cashew trees with other crops may therefore carry risks such as competition for water, mineral elements, light, etc. Consequently, only a well-thought-out crop association that takes these risks into account and aims for a more efficient use of natural resources would be appropriate (Keli et al, 2005). According to Mansaray et al (2022), the benefits of crop association are observed when the components of the system exhibit different morphological growth patterns and strongly compete for natural resources at different times.…”
Section: Introductionmentioning
confidence: 99%